PELATIHAN MANAJEMEN USAHA DAN ETIKA BISNIS SANTRIPRENEUR PADA PONDOK PESANTREN MUKMIN MANDIRI KOTA SIDOARJO - Nadia Asandimitra; Widyastuti Widyastuti; Yessy Artanti; Agus Frianto; Monika Tiarawati; Nindria Untarini (Jurnal Abdi Insani, 2022)
Islamic boarding schools are one of the institutions with the strategic potential to support national economic development, one of which is the development of modern industrial entrepreneurs in the boarding school setting. Many Islamic boarding schools have formed cooperatives, created small and medium-sized business units or industries, and had business incubators. In fact, they frequently disregard the records in the books of financial statements, making future business developments difficult to plan. This community service activity aims to provide solutions to problems encountered by Islamic boarding schools, such as business management management in terms of determining product selling prices, financial management by compiling simple financial reports, and ethics or norms in running a business in accordance with Islamic Sharia. The activity method is carried out in several stages, including observation and preparation, partner problem analysis, coordination, and training. The outcomes of this community service activity show that the majority of participants understand business management and business ethics. The routine activities of recording financial statements demonstrate their comprehension. Although some participants have not yet recorded financial statements on a regular basis, they have a strong desire to do so. Most of them believe that by regularly recording financial reports and adhering to business norms, they can help smooth and change the business mindset. This business management and business ethics training allows students and business actors at Mukmin Mandiri Islamic boarding school to manage their finances more neatly and orderly, as well as carry out their business activities more ethically.